2015
DOI: 10.1002/pds.3805
|View full text |Cite
|
Sign up to set email alerts
|

Standardisation of the FAERS database: a systematic approach to manually recoding drug name variants

Abstract: The millions of reports enclosed in the FAERS contain valuable information that is of interest to pharmacovigilance, toxicology and post-marketing surveillance researchers. With the standardisation of the drug nomenclature, the database can be better utilised by research groups around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…The FAERS AEOLUS database, containing 3,526 drugs mapped to the RxNorm drug vocabulary and 17,710 unique AE terms, was installed as a MySQL database (58). Drugs were mapped to ChEMBL parent compounds, which group different salt forms of the same drug and link to a unique molecular parent structure, using the mapping between RxNorm concepts and DrugBank identifiers provided by the RXNCONSO file from the RxNorm vocabulary (RxNorm_full_12032018, downloaded from (59)) and UniChem (60), as well as direct matches between RxNorm compound names and synonyms and ChEMBL pref_name, compound_names and synonyms.…”
Section: Faersmentioning
confidence: 99%
“…The FAERS AEOLUS database, containing 3,526 drugs mapped to the RxNorm drug vocabulary and 17,710 unique AE terms, was installed as a MySQL database (58). Drugs were mapped to ChEMBL parent compounds, which group different salt forms of the same drug and link to a unique molecular parent structure, using the mapping between RxNorm concepts and DrugBank identifiers provided by the RXNCONSO file from the RxNorm vocabulary (RxNorm_full_12032018, downloaded from (59)) and UniChem (60), as well as direct matches between RxNorm compound names and synonyms and ChEMBL pref_name, compound_names and synonyms.…”
Section: Faersmentioning
confidence: 99%
“…The files from January/2003 to September/2012 were made available by Wong et al, who standardized the names of the drugs reported within this period [23]. The files from October/2012 to June/2016 were in turn directly downloaded from the FDA website.…”
Section: Data Preparationmentioning
confidence: 99%
“…To address the issue of duplicate reports and the lack of standardization of drug names, we performed a manual and detailed reorganization of drug name variants in the database. 23 The open source software, OpenRefine (previously Google Refine; version 2.5) was utilized to organize and standardize medication brand names and common misspellings to reflect their relevant active ingredients. 23 All active ingredients were defined according to the World Health Organization (WHO) Anatomical Therapeutic Chemical (ATC) classification.…”
Section: Data Preparationmentioning
confidence: 99%
“…23 The open source software, OpenRefine (previously Google Refine; version 2.5) was utilized to organize and standardize medication brand names and common misspellings to reflect their relevant active ingredients. 23 All active ingredients were defined according to the World Health Organization (WHO) Anatomical Therapeutic Chemical (ATC) classification. Drugs that could not be standardized according to this classification or were not recognized as a medicinal product were left verbatim.…”
Section: Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation